(untitled) (Archaeologia Adriatica, 2010)
I will use the opportunity in the fourth number of the Archaeologia Adriatica journal which is dedicated to my friend and colleague J. Belošević to pay attention to the finds which were found at the sea bottom as a consequence of various shipwrecks or as discarded or lost objects in the Early Middle Ages period when Croatian state developed and existed. Monuments from this period belong to rich scope of the study and research of my colleague J. Belošević. In this case by underwater finds I refer to a specific category of monuments that I have already written about, and which can be dated to the mentioned period on the basis of analogies. Namely these are amphorae which exhibit considerable differences regarding their size, i.e. capacity from the earlier types dated from the 5th to 7th centuries. These Byzantine amphorae, as they are usually referred to, have characteristic massive handles which are usually higher than the vessel’s opening whereas base of the amphora is oval in shape, without pointed end characteristic of the earlier amphorae. Forms are usually piriform or ovoid, and their height usually does not exceed 40 cm. Remains of a shipwreck with amphorae of this type were discovered near the island of Mljet in the mid-1970s and the site had already been devastated. I discovered another site with the remains of the Byzantine amphorae and some other objects in the sea in front of the Ždrijac site in the vicinity of Nin when I was working as a curator of a regional archaeological collection in Nin in the 1960s. Byzantine amphorae were also found in 1995 in the Bay of Pijan in Savudrija where rescue underwater archaeological excavations of an important ancient port near Aquileia were undertaken due to building and extending a quay. Great part of the remaining amphorae which I present in this paper are older finds without exact data about the findspot and circumstances of discovery, such as the upper segment of an amphora from Umag or an oblong amphora with large handles which are significantly higher than its opening from Poreč (presently in the Regional Museum in Poreč). Three almost identical amphorae have piriform bodies and massive handles with a triangular cross-section which are higher than the amphora’s opening. One of them was found near the island of Žut long time ago, presently it is in the Šibenik City Museum, the second was taken out of the sea in a fishing net between the islands of Silba and Olib, and the third one is from the Trogir port. There are several more amphorae corresponding to these finds: upper segment of an amphora from Ždrijac in Nin and two somewhat larger amphorae, one of which was found near the island of Ošljak near Zadar long ago (presently in the Archaeological Museum in Zadar) and the other from the Kovačić collection on the island of Hvar. A larger segment of a smaller oblong amphora of the similar shape was found in the 1970s near the island of Vela Arta near Murter. An upper segment of an amphora with a distinct neck and opening and large massive handles with triangular cross-section was found in the sea near the cape of Gospa od Gradine in Rogoznica, presently also in the Šibenik City Museum. We also need to mention finds from the port of Hvar found in 1991 and amphorae from the churches of St. Michael in Ston, St. George on the island of Vis and St. Barbara in Trogir. Underwater explorations along the Asia Minor coastline and in the Black Sea brought to light similar examples of amphorae on the basis of which N. Günsenin and Ch. Bakirtzis created a chronology, classifying them into several types dated from the 9th to 13th centuries. For an amphora from the collection of the Franciscan Monastery on the island of Krapanj we can find closer analogies, and probably also production centers on Peloponnesus. Without individual analysis of each of our amphorae, we can easily notice difference in the height of the handles which are often higher than the amphora’s opening. Other evident differences include size and forms of amphorae as well as their diversity in relation to amphorae from the same period found in Turkish/Pontic region and the remaing part of the Balkans. These insights about the typological differences between our amphorae and the aforementioned ones in the Asia Minor region open up possibilities for hypothesizing about other, possibly local workshop centers in the area of today’s Albanian littoral or the rest of the eastern Adriatic coast. All together, our coast shows the most impressive picture of maritime trade in the early medieval period on the basis of density of finds of the mentioned amphorae. Trade with glass products was also present in this period along our coast as indicated by the remains of a shipwreck near Cape Stoba on the island of Mljet where a certain amount of glass sets was found together with amphorae. Some of complete glass items found on a shipwreck near Serçe Limani can be related to some finds from the terrestrial sites on the basis of analogies, such as a glass flask from the grave (no. 322) at the great necropolis from Ždrijac in Nin which can be related to the workshop centres of the eastern Mediterranean since similar flask was found on the shipwreck from Serçe Limani in Turkey.